A tecpr2 knockout mouse exhibits age-dependent neuroaxonal dystrophy associated with autophagosome accumulation. Issue 10 (3rd October 2021) - Tamim-Yecheskel, Bat-Chen; Fraiberg, Milana; Kokabi, Kamilya; Freud, Saskia; Shatz, Oren; Marvaldi, Letizia; Subic, Nemanja; Brenner, Ori; Tsoory, Michael; Eilam-Altstadter, Raya; Biton, Inbal; Savidor, Alon; et al.
ABSTRACT: Mutations in the coding sequence of human TECPR2 were recently linked to spastic paraplegia type 49 (SPG49), a hereditary neurodegenerative disorder involving intellectual disability, autonomic-sensory neuropathy, chronic respiratory disease and decreased pain sensitivity. Here, we report the generation of a novel CRISPR-Cas9 tecpr2 knockout ( tecpr2 −/− ) mouse that exhibits behavioral pathologies observed in SPG49 patients. tecpr2 −/− mice develop neurodegenerative patterns in an age-dependent manner, manifested predominantly as neuroaxonal dystrophy in the gracile (GrN) and cuneate nuclei (CuN) of the medulla oblongata in the brainstem and dorsal white matter column of the spinal cord. Age-dependent correlation with accumulation of autophagosomes suggests compromised targeting to lysosome. Taken together, our findings establish the tecpr2 knockout mouse as a potential model for SPG49 and ascribe a new role to TECPR2 in macroautophagy/autophagy-related neurodegenerative disorders.